ANALISIS PELAKSANAAN KEBIJAKAN MELALUI DISKRESI OLEH PEJABAT NEGARA - Parlindungan S, Gokma Toni (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Referring to the discussed material above, several conclusions can be drawn regarding the internalization of the Rule of Law elements into efforts to hold accountable the abuse of authority in discretion (decisions and/or actions) by Government Officials related to corruption offenses involving financial losses to the state. This can be considered a rational thought result inseparable from the first influence, legal politics [outline or basic plan of government's agenda] in the UUAP related to the use of discretion by government bodies or officials in the form of legal policy or official guidelines containing the outline and basic plan of the government as the basis for the implementation of government administration itself. Second, the law enforcement process for officials suspected of committing corruption offenses involving financial losses to the state through the use of discretion must first adhere to the legal norms used by officials in their activities, namely administrative law which conceptually has principles, norms, and characteristics different from criminal law. Third, the issue of freedom to make policies (freis ermessen-discretionary power) falls within the domain of administrative law and thus cannot serve as a basis for criminal prosecution. Therefore, decision-makers and/or actions (discretion) cannot be easily criminalized, ensuring that government bodies and/or officials are not hindered in innovating government administration. Keywords: Analysis, Policy, Discretion, Government Officials.